2‐Arachidonoyl glycerol potently induces cholecystokinin secretion in murine enteroendocrine STC‐1 cells via cannabinoid receptor CB1. Issue 6 (17th September 2021) - Ochiai, Keita; Hirooka, Rina; Sakaino, Masayoshi; Takeuchi, Shigeo; Hira, Tohru
Abstract: Cholecystokinin (CCK) is a peptide hormone secreted from enteroendocrine cells and regulates the exocrine pancreas, gastric motility, and appetite. Dietary triacylglycerols are hydrolyzed to fatty acids (FA) and 2‐monoacylglycerols (2‐MAG) in the small intestine. Although it is well known that FA stimulate CCK secretion, whether 2‐MAG have the CCK‐releasing activity remains unclear. We examined the CCK‐releasing activity of four commercially available 2‐MAG in a murine CCK‐producing cell line, STC‐1, and the molecular mechanism underlying 2‐MAG‐induced CCK secretion. CCK released from the cells was measured using ELISA. Among four 2‐MAG (2‐palmitoyl, 2‐oleoyl, 2‐linoleoyl, and 2‐arachidonoyl monoacylglycerols) examined, 2‐arachidonoyl glycerol (2‐AG) potently stimulated CCK secretion in a dose‐dependent manner. Structurally related compounds, such as 2‐arachidonoyl glycerol ether and 1‐arachidonoyl glycerol, did not stimulate CCK secretion. Both arachidonic acid and 2‐AG stimulated CCK secretion at 100 μM, but only 2‐AG did at 50 μM. 2‐AG‐induced CCK secretion but not arachidonic acid‐induced CCK secretion was attenuated by treatment with a cannabinoid receptor 1 (CB1) antagonist. These results indicate that a specific 2‐MAG, 2‐AG, directly stimulates CCK secretion via CB1.